2020
DOI: 10.3389/fpls.2020.01018
|View full text |Cite
|
Sign up to set email alerts
|

Temperature-Dependent Compatible and Incompatible Pollen-Style Interactions in Citrus clementina Hort. ex Tan. Show Different Transglutaminase Features and Polyamine Pattern

Abstract: In clementine, failure of fertilization can result in parthenocarpic fruit development, which has several advantages, such as seedless fruit, longer shelf-life, and greater consumer appeal. Recently, S-RNases have been identified in Citrus grandis , thus revealing that the self-incompatibility (SI) reaction relies on the S-RNase gametophytic mechanism. The fundamental role of environmental factors, mostly temperature, in determining the numbers of pollen tubes reaching the ovary is also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 71 publications
0
17
0
Order By: Relevance
“…The conclusion concerning a gametophytic SI system in citrus with the SI locus located at the beginning of chromosome 7 of the clementine reference genome proposed by Liang et al [46] is therefore strongly confirmed by our study. However, the influence of environmental conditions on pollen-pistil interactions has already been documented [41,73,74] and different transglutaminase features and polyamine pattern were recently described depending on the prevailing temperature during pollination [41]. Additional studies are needed to gain a full understanding of the pollen-pistil interaction in different citrus species under different environments.…”
Section: Segregation Distortion In the Male Parent Revealed A Genomic Region Involved In Self-incompatibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…The conclusion concerning a gametophytic SI system in citrus with the SI locus located at the beginning of chromosome 7 of the clementine reference genome proposed by Liang et al [46] is therefore strongly confirmed by our study. However, the influence of environmental conditions on pollen-pistil interactions has already been documented [41,73,74] and different transglutaminase features and polyamine pattern were recently described depending on the prevailing temperature during pollination [41]. Additional studies are needed to gain a full understanding of the pollen-pistil interaction in different citrus species under different environments.…”
Section: Segregation Distortion In the Male Parent Revealed A Genomic Region Involved In Self-incompatibilitymentioning
confidence: 99%
“…Molecular and transcriptomic studies revealed that different molecules and gene families may be involved in SI mechanisms in citrus. Among the factors involved in the SI mechanism, a role for transglutaminases and polyamines and particularly spermidine was proposed [39][40][41]. Over the last 15 years, comparative transcriptome approaches have been applied to identify the genes and proteins involved in the SI response.…”
Section: Introductionmentioning
confidence: 99%
“…indicate that constant high and low temperatures appear to have an effect on the incompatibility reaction by affecting the place where pollen tubes are arrested [59 cently, Aloisi et al [60] indicated that temperature contributed to a different activat the self-incompatibility reaction in C. clementina, occurring at an optimal temperatu 25 °C and bypassed at 15 °C. The incompatible reaction resulted in enhancement o transglutaminase enzyme activity and levels of conjugated polyamines when com to cross-pollination [60]. However, more research is needed to understand how env mental conditions can influence the self-incompatibility reaction in citrus.…”
Section: Self-incompatibilitymentioning
confidence: 99%
“…In the pollen tube of Angiosperms, callose is deposited as a tubular sheath surrounding the pollen tube anks. Callose is usually absent at the apex and subapex of pollen tubes, and it is a common feature that incidental presence in those regions is associated with cessation of growth (Geitmann and Steer 2006;Mandrone et al 2019;Aloisi et al 2020). The tubular sheath of callose enhances the tensile strength of the cell wall.…”
Section: Introductionmentioning
confidence: 99%